What Are the Oxidizing Intermediates in the Fenton and Fenton-like Reactions? A Perspective - Dan Meyerstein (MDPI AG, 2022)
The Fenton and Fenton-like reactions are of major importance due to their role as a source of oxidative stress in all living systems and due to their use in advanced oxidation technologies. For many years, there has been a debate whether the reaction of FeII(H2O)62+ with H2O2 yields OH• radicals or FeIV=Oaq. It is now known that this reaction proceeds via the formation of the intermediate complex (H2O)5FeII(O2H)+/(H2O)5FeII(O2H2)2+ that decomposes to form either OH• radicals or FeIV=Oaq, depending on the pH of the medium. The intermediate complex might also directly oxidize a substrate present in the medium. In the presence of FeIIIaq, the complex FeIII(OOH)aq is formed. This complex reacts via FeII(H2O)62+ + FeIII(OOH)aq → FeIV=Oaq + FeIIIaq. In the presence of ligands, the process often observed is Ln(H2O)5−nFeII(O2H) → L•+ + Ln−1FeIIIaq. Thus, in the presence of small concentrations of HCO3− i.e., in biological systems and in advanced oxidation processes-the oxidizing radical formed is CO3•−. It is evident that, in the presence of other transition metal complexes and/or other ligands, other radicals might be formed. In complexes of the type Ln(H2O)5−nMIII/II(O2H−), the peroxide might oxidize the ligand L without oxidizing the central cation M. OH• radicals are evidently not often formed in Fenton or Fenton-like reactions.